Influence Of Learning Strategy And Independence Learning On The Learning Outcomes of Islamic Education - Rusydi Ananda; Fitri Hayati (CV. Pusdikra Mitra Jaya, 2022)
In applied learning, it can be seen that there are differences in students' abilities in absorbing teaching materials from the teacher. So there needs to be a strategy to overcome independence in student learning. This study aims to determine and describe: (1) the effect of the implementation of learning strategies on learning outcomes of Islamic Education, (2) the effect of learning independence on Islamic s Education learning outcomes, and (3) the influence of learning strategies and learning independence on learning outcomes Islamic education. The population of this study was all students of class V Al-Hijrah Deli Serdang consisting of 3 classes. Based on the cluster Random sampling technique. The research instrument is a test used to obtain learning outcomes data and a questionnaire to obtain student learning independence data. The analysis technique is an analysis of variance. The results showed: (1) the average Islamic Education learning outcomes of students taught with the CIRC learning strategy were higher than the average Islamic Education learning outcomes of students taught with expository learning strategies, (2) the average Islamic Education learning outcomes of students with high learning independence are higher than learning outcomes of students with low learning independence and (3) there is an interaction between learning strategies and learning independence.